Rumus Geligi Berudu Sebagai Karakter Identifikasi: Studi Kasus Pada Berudu Hydrophylax chalconotus (Schlegel, l837) dan Duttaphrynus melanostictus (Schneider, 1799) - Eprilurahman, Rury (Fakultas Biologi Universitas Gadjah Mada, 2010)
Character of anuran larvae (or known as tadpoles) that can be used for identification is labial tooth row formula (LTRF) from its mouthpart. This character was written and widely used in the amphibian field guides as identification character into species. Sometimes, this could lead to misidentification due to different formulas within one species. Hydrophylax chalconotus (Anura: Ranidae) and Duttaphrynus melanostictus (Anura; Bufonidae) are common anurans species around the human activity area such as garden, pool, and other habitats. This research was aimed at describing the development of labial tooth row formula (LTRF) of H. chalconotus and D. melanostictus during metamorphosis. Specimens were taken from several locations in Sleman Regency, Yogyakarta Special Province. This research was done by collecting and rearing tadpoles from eggs into larvae. The observation was conducted using stereo microscope. Premetamorphosis phase (stage 17-35) was determined based on Gosner (1960), while LTRF was determined based on Iskandar (1995). The LTRF development of each species was noted and recorded. Results show that Jirst LTRF of H. chalconotus could be seen from stage 25 and gradually changed into complex structure until stage 35. Meanwhile, first LTRF of D. melanostictus could be shown from the stage 24 and remain unchanged until stage 35. Based on the observation, it can be concluded that the variation of LTRF was the result of development, and that some differences on same stages indicating variation within species. Thus, it is recommended that identification using LTRF should also consider the stage of the tadpoles development. This preliminary researh should be followed by similar research using different species.